MODEL INQUIRY BASED LEARNING GUNA MENINGKATKAN KECAKAPAN BERPIKIR KRITIS PADA PEMBELAJARAN AKIDAH AKHLAK DI MTS NU PANCOR - Agus Sulthoni Imami; Homaidi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Inquiry Based Learning model and its contribution to improving critical thinking skills in Akidah Akhlak learning at MTs NU Pancor. The study employed a qualitative approach with a case study design to gain an in-depth understanding of the learning process and the development of students’ critical thinking skills. The research subjects consisted of one Akidah Akhlak teacher as the main informant and eight students as supporting informants selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and documentation. Data analysis used the Miles, Huberman, and Saldaña model through the stages of data reduction, data display, and conclusion drawing. Data validity was tested through source triangulation, technique triangulation, and member checking. The results showed that the implementation of the Inquiry Based Learning model was able to improve students’ critical thinking skills, as reflected in their ability to ask questions, analyze problems, present logical arguments, and relate learning materials to daily life. In addition, this learning model created a more active, interactive, and reflective learning atmosphere, enabling students to become more engaged in exploration and discussion processes based on Islamic values.